Effect of different recovery interventions among road cycling riders / Khairal Afiq Jamal Abd Haziq - Jamal Abd Haziq, Khairal Afiq (2017)
Post exercise recovery is important for endurance athletes such as road race cyclists that participated in back-to-back days of racing. The restoration of physiological functions of an athlete can be speed-up by implementing post exercise recovery interventions such as cryotherapy (CRYO), passive (PAS) and active (ACT) recovery. It is well documented that these interventions positively affect the recovery of an athlete in laboratory based. The purpose of this study is to investigate the effects of three different types of recovery interventions (CRYO, PAS and ACT) on blood lactate concentration and heart rate among road race cyclists following the actual road race cycling. Ten (10) well trained junior road cycling race athletes aged between 15 to 18 years old participated in this study. The participants have completed three sessions of 90 km cycling, which each session was separated by a week (7 days). Each session has a different implementation of post exercise recovery method (CRYO, PAS or ACT). After completing each race session, the post-race blood lactate concentration and heart rate of each cyclist was taken and recorded, followed by 15 minutes of post exercise recovery session. Heart rate was taken and recorded again after the next 30 minutes of follow up phase. Results showed that these three interventions effectively reduced post-race blood lactate concentration and heart rate among road race cyclists. However, higher reduction of both variables was found in CRYO compared to PAS and ACT (p<0.05). These three types of recovery interventions could be used by road race cyclists during the initial phase (first 15 minutes) of post exercise recovery following road race cycling, depends on the individual physiological responses.